Stratigraphic and geochemical constraints on the relative age of the Margaree Shear Zone in western Cape Breton Island, with implications for the early evolution of the Maritimes Basin - Lynch, Gregory (Atlantic Geology, 1996)
The Margaree Shear Zone is interpreted to be a thick, brittle-ductile low-angle extensional fault which was active in the Mid to Late Devonian at the lime of initiation of the Maritimes Basin. In western Cape Breton Island, the fault separates two distinct basalt assemblages: low-grade to non-metamorphosed intra-continental basalts of the Upper Devonian Fisset Brook Formation occur in the hangingwall, whereas more primitive Ordovician-Sil-urian basalts, which were metamorphosed in Early Devonian time, to upper green schist grade occur in the foot-wall. Major and trace element geochemistry from mylonitic basalt near the top of the shear zone demonstrate that the Fisset Brook Formation has been affected by the shearing. In particular the mylonitcs of Fisset Brook affinity are characterized by higher Ti, Zr, P, Y, and Ga contents, and lower Ni, Cr, and Mg values compared to the older basalts. Elemental plots arc represented as ratios to eliminate enrichment or dilution factors caused by mobile elements such as Si, Ca, K, and Na. The age of the shear zone is further constrained in the region by an unconformity, which displays Tournaisian conglomerate of the Horton Group resting directly on the flat-lying mylonite, the former composed of clasts including mylonite as well as non-deformed vesicular basalt of the Fisset Brook Formation.